Propylene/propane separation by vacuum swing adsorption using Cu-BTC spheres - M. G. Plaza (2012)
Cu-BTC MOF is an appealing candidate to carry out propane/propylene separation by adsorption due to its high adsorption capacity and propylene selectivity. In this work a new sample of Cu-BTC, synthesised and shaped into spheres by the Korean Research Institute of Chemical Technology (KRICT) is studied for this commitment. The sample under evaluation presents the highest propylene specific adsorption capacity known up to date for a shaped material (up to 8 mol kg(-1) of dry adsorbent at 323 K). A mathematical model is proposed that adequately describes breakthrough experiments. This model has also been used to simulate an experimental 5-step VSA cycle conceived to produce polymer grade propylene. Although this cycle presents low recoveries, the validated model can be used as a base for VPSA design.